(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ABSTRACT This article that addresses the challenges faced by students when learning a foreign language, particularly English, and offers solutions to improve speaking skills through various apps and online resources. By incorporating technology into language learning, students can access a wide range of tools and resources to enhance their language proficiency, including speech practice, vocabulary building, grammar exercises, and real-life conversation opportunities. This approach can help students overcome language barriers and develop their speaking skills effectively. The article seems to provide valuable insights into how technology can support language learning and offer practical tips for students looking to improve their language skills.